1998
DOI: 10.1172/jci1076
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle peroxisome proliferator- activated receptor-gamma expression in obesity and non- insulin-dependent diabetes mellitus.

Abstract: (a) skeletal muscle PPARgamma1 expression does not differ between normal and diabetic subjects, and is not induced by short-term hyperinsulinemia; (b) skeletal muscle PPARgamma1 expression was higher in subjects whose percent body fat exceeded 25%, and this may be a compensatory phenomenon in an attempt to maintain normal insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 38 publications
(38 reference statements)
5
61
0
Order By: Relevance
“…In agreement with our previous finding in muscle, a recent report also found PPARg mRNA in adipose tissue to be increased after a 3-h hyperinsulinaemic, euglycaemic clamp [38]. Other investigators found no change in skeletal muscle PPARg1 mRNA after 5 h of hyperinsulinaemia [39]. This discrepancy could also represent a potential transient nature of the insulin effect to increase gene expression, it could have returned to baseline by 5 h. There are other examples of such transient responses in gene expression to insulin exposure [40].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our previous finding in muscle, a recent report also found PPARg mRNA in adipose tissue to be increased after a 3-h hyperinsulinaemic, euglycaemic clamp [38]. Other investigators found no change in skeletal muscle PPARg1 mRNA after 5 h of hyperinsulinaemia [39]. This discrepancy could also represent a potential transient nature of the insulin effect to increase gene expression, it could have returned to baseline by 5 h. There are other examples of such transient responses in gene expression to insulin exposure [40].…”
Section: Discussionsupporting
confidence: 92%
“…10 On the contrary, other studies found no correlation between subcutaneous or omental adipose tissue PPARg mRNA and BMI. 11,13,46 Also, in Rhesus monkeys there was no correlation between total PPARg adipose tissue mRNA expression and obesity, but the ratio of PPARg2/total PPARg was positively correlated with obesity and fasting insulin concentration. 47 In addition, in obese human subjects, the ratio of PPARg expression in omental/subcutaneous adipose PPARgamma agonistsFadipogenic treatment of type II diabetes TM Larsen et al tissue was increased compared to normal weight subjects, suggesting that the relative PPARg expression is increased in omental fat in obesity.…”
Section: Pparg Activation Induces Transcription Of Genes Involved In mentioning
confidence: 94%
“…10 These results were corroborated in other studies in humans. [11][12][13] In addition to adipose tissue, PPARg is expressed at rather high levels in the large intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical procedures. Plasma and infusate [ 3 H]glucose specific activity were determined as previously described (34). Insulin was measured by a double-antibody technique (35).…”
Section: Methodsmentioning
confidence: 99%